MASTER: a triple heterodyne receiver for astronomy in the millimetre and sub-millimetre domain - BATTISTELLI, Elia Stefano; ZANNONI M; BOELLA G; GERVASI M; PASSERINI A; SIRONI G; ANDREONE D; BRUNETTI L; LACQUANITI V; MAGGI S; STENI R; NATALE V; et al. (Publications of the Astronomical Society of Australia, 2001)
A progress report of the MASTER project is presented here. MASTER is a system of three heterodyne receivers based on SIS (superconductor–insulator–superconductor) tunnel junction mixers. In our instrument these mixers will allow direct down-conversion from 94, 225, and 345 to 1.5 GHz, the IF where the signal will be detected. This instrument, coupled to a 2–4m telescope like the one proposed for the DOME C base in Antarctica and in conjunction with an Acusto Optical Spectrometer, can be used to detect emission lines associated with molecular clouds in the interstellar medium. The current status of a 94 GHz receiver, the prototype of MASTER, will be presented too. The study of the optical coupling between the receiver and MITO telescope in the Italian Alps will also be described.